Practitioner Experience With Mistreated Older Adults Who Have Dementia: Understanding Contextual Influences and Consequences - Lindenbach, Jeannette (Journal of interpersonal violence, 2022)
Studies of mistreatment of older adults have revealed alarmingly higher prevalence rates of mistreatment of those who have dementia. When the mistreatment occurs within the context of the home and is perpetrated by a family caregiver, it may remain hidden and only be discovered by the health and social service practitioners who have access to the home. Understanding the contexts within which this mistreatment occurs, and the influence of these contexts on the experience of these practitioners as well as on the resulting outcomes for mistreated older adults, has received little attention in the literature. This qualitative study, framed by critical social theory, aimed to answer the following research question: What are the contextual influences on practitioner experience with mistreatment of older adults with dementia by a caregiver within the home? Specifically, this study explored contextual influences within a Canadian province, where there is neither specific adult protective legislation nor infrastructure when mistreatment occurs within the home. Data were collected via semi-structured interviews, journals, and focus groups with 51 practitioners from various disciplines providing services to mistreated older adults with dementia in their homes. Theoretical thematic analysis led to the discovery of five contextual themes influencing the experience: the privileged burden of seeing behind closed doors; a domestic problem within a societal context; interprofessional challenges; a history of stagnation, losses, and systems failure; and a legislative complexity and oppression. Understanding these contextual influences is crucial to supporting practitioners, who, although entrusted to protect mistreated older adults, describe powerlessness within current contexts. This understanding is needed to improve outcomes for mistreated older adults with dementia.